Menakar Kemampuan Bernalar Kritis dan Literasi Murid SD: Studi Kasus Tulisan Refleksi Memaknai Cerita Bergambar “Ketangguhan Wisnu” - Ignatia Esti Sumarah; Bonifatius Sigit Yuniharto (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: The significant decline in Indonesia's reading literacy scores in the 2022 PISA data, coupled with the challenges of digital disruption for elementary school students, has become a primary urgency for strengthening the School Literacy Movement (GLS). This narrative research aims to: (1) analyze and map the relevance between students' personal experiences and the indicators of critical thinking found in characters; (2) describe the linguistic profiles of the students' writing to observe how they construct ideas of resilience through word choice and language style. The research subjects were selected using a non-probability sampling technique, specifically purposive sampling, based on the criterion of narrative depth. The participants included students from grade 4 at SD Negeri Ngringin (2 students), grade 5 at SD Negeri 1 Jatilawang (9 students), and grade 6 at SD Negeri Sariharjo (2 students). The results indicate that the use of the picture storybook "Ketangguhan Wisnu" effectively improves students' reflective literacy and critical thinking skills through strong connections between personal experiences and resilience indicators, such as self-confidence, emotional regulation, and the persistence to bounce back from failure. Substantively, students were able to construct ideas about resilience well; however, their linguistic profiles revealed that technical writing skills are still dominated by errors that do not comply with PUEBI standards amidst the challenges of digital disruption.Abstrak: Penurunan signifikan capaian literasi membaca Indonesia pada data PISA 2022 serta tantangan disrupsi digital pada murid sekolah dasar menjadi urgensi utama bagi penguatan Gerakan Literasi Sekolah (GLS). Penelitian naratif ini bertujuan: (1) menganalisis dan memetakan keterkaitan (relevansi) antara pengalaman personal murid dengan indikator bernalar kritis yang ada pada tokoh. (2) Mendeskripsikan profil kebahasaan hasil tulisan murid untuk melihat bagaimana mereka mengonstruksi gagasan tentang ketangguhan melalui pilihan kata dan gaya bahasa. Subjek dalam penelitian ini menggunakan teknik non-probability sampling, khususnya purposive sampling. Subjek dipilih berdasarkan kriteria kedalaman narasi. Subjek penelitian melibatkan murid dari kelas 4 SD Negeri Ngringin (2 murid), kelas 5 SD Negeri 1 Jatilawang (9 murid), dan kelas 6 SD Negeri Sariharjo (2 murid). Hasil penelitian menunjukkan bahwa penggunaan buku cerita bergambar “Ketangguhan Wisnu” efektif meningkatkan literasi reflektif dan kemampuan bernalar kritis murid melalui keterkaitan yang kuat antara pengalaman personal dengan indikator resiliensi, seperti keyakinan diri, regulasi emosi, dan kegigihan untuk bangkit dari kegagalan. Secara substantif, murid mampu mengonstruksi gagasan tentang ketangguhan dengan baik; namun, profil kebahasaan hasil tulisan mereka menunjukkan bahwa keterampilan teknis penulisan masih didominasi oleh kesalahan yang belum sesuai dengan kaidah PUEBI di tengah tantangan disrupsi digital.